Utilization of Leaf Litter as Growth Media for Suren (Toona sureni Merr.) Rhizosphere Fungi Isolates - Gusmiati; Muh. Restu; Siti Halimah Larekeng; Budirman Bachtiar; Muhammad Bima Akzad (Talenta Publisher, 2020)
Leaf litter or organic matters can decompossed by microorganisms like fungi.This study aims to determine the ability of growth and the rate of decomposition of Suren (Toona sureni Merr.) rhizosphere fungi isolates on various organic media. The testing process was carried out at the Biotechnology and Tree Breeding Laboratory, Faculty of Forestry, Hasanuddin University, Makassar. The research method consisted of making fungi growing media, rejuvenating isolates and making organic media from teak leaf litter (Tectona grandis), Jabon (Anthocephalus cadamba), and Mahogany (Swietenia macrophylla). The highest growth of mycelium was found in Fusarium sp. The growth of the five best fungi isolates in the formulation of mahogany leaf litter and the highest average decomposition rate in the combination treatment of mahogany leaf litter and Fusarium sp.